The Grounded Expertise Components Approach in the Novel Area of Cryptic Crossword Solving - Friedlander, Kathryn J.; Fine, Philip A. (Frontiers in Psychology, 2016)
This paper presents a relatively unexplored area of expertise research which focuses on the solving of British-style cryptic crossword puzzles. Unlike its American ‘straight-definition’ counterparts, which are primarily semantically-cued retrieval tasks, the British cryptic crossword is an exercise in code-cracking detection work. Solvers learn to ignore the superficial ‘surface reading’ of the clue, which is phrased to be deliberately misleading, and look instead for a grammatical set of coded instructions which, if executed precisely, will lead to the correct (and only) answer. Sample clues are set out to illustrate the task requirements and demands. Hypothesized aptitudes for the field might include high fluid intelligence, skill at quasi-algebraic puzzles, pattern matching, visuospatial manipulation, divergent thinking and breaking frame abilities. These skills are additional to the crystallized knowledge and word-retrieval demands which are also a feature of American crossword puzzles. The authors present results from an exploratory survey intended to identify the characteristics of the cryptic crossword solving population, and outline the impact of these results on the direction of their subsequent research. Survey results were strongly supportive of a number of hypothesized skill-sets and guided the selection of appropriate test content and research paradigms which formed the basis of an extensive research program to be reported elsewhere. The paper concludes by arguing the case for a more grounded approach to expertise studies, termed the Grounded Expertise Components Approach. In this, the design and scope of the empirical program flows from a detailed and objectively-based characterization of the research population at the very onset of the program.